One-Pot Synthesis of Nitriles from Aldehydes Catalyzed by Deep Eutectic Solvent - Patil, Umakant B.; Shendage, Suresh S.; Nagarkar, Jayashree M. (Synthesis, 2013)
The choline chloride–urea (1:2) based deep eutectic mixture as an efficient and ecofriendly catalyst for the one-pot synthesis of nitriles from aldehydes under solvent-free conditions under both conventional and microwave irradiation; the products were obtained in good to excellent yields.
Keywords: nitriles; deep eutectic solvent; aldehydes; hydroxylamine hydrochloride; microwave